Synergistic Combination of Histone Deacetylase Inhibitor Suberoylanilide Hydroxamic Acid and Natural Flavonoid Curcumin Exhibits Anticancer and Antibacterial Activity - YALÇIN, AHMET SUHA; YILMAZ GÖLER, AYŞE MİNE (BENTHAM SCIENCE PUBL LTD, 2021)
Background and Objective: Curcumin is an effective anti-cancer agent used in thyroid cancer treatments. However, its use in clinical applications is limited due to low solubility and bioavailability. In this study, a novel combination strategy was applied by combining curcumin with Suberoylanilide Hydroxamic Acid (SAHA) to increase both bioavailability of curcumin and the efficiency of SAHA, which have limited efficiency when used alone. Methods: MTT assay was used to determine the cell viability of B-CPAP cells upon treatment with SAHA, curcumin and their combinations. Synergistic interactions between two agents were analyzed by Calcusyn software. Apoptosis and cell cycle assays were measured by flow cytometry. Expressions of apoptotic and cell cycle-related proteins (PARP, P21/CDKN1A/WAF1, P27/KIP1) were examined by western blot analysis. Broth microdilution assay was performed to determine Minimum Inhibitory Concentration (MIC) values against S. aureus. Results: Based on MTT assay, IC50 values for SAHA and curcumin were determined as 0.91 mu M and 20.97 mu M, respectively. The combination index CI value was determined as 0.891 in B-CPAP cells, which demonstrate synergistic activity. The apoptotic effect was achieved by combination treatment (51.85%) on B-CPAP cells using half of the dose required for SAHA and curcumin alone. Combination treatment showed a significant increase in the percentage of B-CPAP cells in the S-phase due to cell arrest. Cleaved-PARP, P21/CDKN1A/ WAF1 and P27/KIP1 protein expressions were upregulated. Curcumin was found to have better anti-microbial activity than SAHA as having a lower MIC value, and checkerboard synergy analysis revealed that the two compounds co-operate synergistically for the in-vitro killing of S. aureus. Conclusion: In the present study, synergistic combinations of SAHA and curcumin were shown to have both anti-cancer and antibacterial activities that would provide a novel thyroid cancer treatment strategy.
Keywords: B-CPAP cells; SAHA; curcumin; apoptosis; anti-microbial activity; histone deacetylase inhibitor